I lived on Butterfly Hill - Agosín, Marjorie (Atheneum Books for Young Readers, 2014)
When her beloved country, Chile, is taken over by a militaristic, sadistic government, Celeste is sent to America for her safety and her parents must go into hiding before they "disappear."